Choroidal naevi complicated by choroidal neovascular membrane and outer retinal tubulation. Issue 8 (18th May 2013) - Papastefanou, Vasilios P; Nogueira, Vanda; Hay, Gordon; Andrews, Richard M; Harris, Martin; Cohen, Victoria M L; Sagoo, Mandeep S
Abstract : Aims: To present the outcomes of a series of patients with choroidal neovascular membrane (CNV) secondary to a choroidal naevus and report the presence of outer retinal tubulation. Methods: In this retrospective series, patients underwent a complete clinical and imaging assessment (fundus photo, fluorescein angiography and optical coherence tomography) and were observed or managed with intravitreal anti-VEGF injections dependent on whether visual acuity was affected. Results: Seventeen patients were included in this study. Of this, 46% (8/17) had classic or predominantly classic CNV and 53% (9/17) had occult or minimally classic CNV. Active treatment with intravitreal anti-VEGF injections was required in 35% (6/17). Visual acuity improved in three eyes by 2–4 Snellen lines, remained stable in one eye and worsened in two eyes by 2 Snellen lines. CNV partially regressed in five cases. In the observation group (65%, 11/17), visual acuity did not change during follow-up period. Outer retinal tubulation was found in 18% (3/17). Conclusions: Anti-VEGF treatment is effective in the management of vision threatening CNV secondary to a choroidal naevus. Functional or anatomical improvement was obtained in 66% of treated eyes. Outer retinal tubulation, noted in 18%, showed the clinical importance of this sign in determining continuation of anti-VEGF treatment.